PENGARUH JUMLAH PENDUDUK DAN PERTUMBUHAN EKONOMI TERHADAP PENDAPATAN ASLI DAERAH (Studi Kasus di Kabupaten/Kota Kawasan Barat Selatan Aceh) - Dedek Hasanur; Zainal Putra (JURNAL EKOMBIS, 2018)
This study aims (a). to determine the effect of population size and economic growth on local revenues in districts / municipalities in Barsela region, (b). to determine the effect of the Number of Residents on the Original Revenue of Regencies / Municipalities in the Barsela region, (c). to determine the effect of Economic Growth on Local Revenue at Regency / City in Barsela region. The data analysis model uses multiple regression analysis. The results of simultaneous research on the variable of population and economic growth have significant and significant effect to PAD. Partially, the number of residents has a positive and significant effect to the original income of the regency / municipality of Barsela of Aceh Province. While partially economic growth does not affect the local revenue.Keywords: population, economic growth and local income